2013
DOI: 10.1166/jnn.2013.6971
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Nickel Nanoparticles by Liquid Phase Plasma Processing

Abstract: In this work, the liquid phase plasma reduction method was applied to prepare the spherical nickel nanoparticles from the solution of nickel chloride. A bipolar pulsed power supply was used to generate discharges in the aqueous solutions. Nickel nanoparticle peaks produced by surface plasmon absorption were observed around 381 nm with electrical discharge. Spherical nickel nanoparticles were mostly observed in this study, pentagonal nanoparticles were also observed occasionally. The TEM image showed that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Two electrodes carried out by means of AC impedance spectroscopy over the frequency range from 200 MHz to 10 Hz with amplitude of 0.1 V. The film thickness varied from 0.007 to 0.02 cm and the sample controlled oven for 1 h before measurement. The ionic conductivity values (s) were calculated from the bulk resistance (R b ), which was determined by equivalent circuit analysis software by using following equation [14]:…”
Section: Electrochemical Charaterizationmentioning
confidence: 99%
“…Two electrodes carried out by means of AC impedance spectroscopy over the frequency range from 200 MHz to 10 Hz with amplitude of 0.1 V. The film thickness varied from 0.007 to 0.02 cm and the sample controlled oven for 1 h before measurement. The ionic conductivity values (s) were calculated from the bulk resistance (R b ), which was determined by equivalent circuit analysis software by using following equation [14]:…”
Section: Electrochemical Charaterizationmentioning
confidence: 99%
“…In many studies, water has been used as a liquid medium due to its unique properties and ease of use [ 16 , 17 , 18 ]. Some researchers have adopted precursors soluble in liquid to obtain metal or metal oxide nanoparticles [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. It has been reported that liquid–plasma interaction produces reducing agents, enabling faster and unique reduction of metal ions [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the synthesis of metal nanoparticles and oxide nanoparticles using in-liquid arc discharge. The use of electrolytes has been studied because it aids in generating stable arc discharge in a liquid environment [ 16 , 17 , 25 , 26 ]. Although electrolytes play an important role in determining the particle-phase composition or morphology, adding electrolytes complicates the reaction by introducing many electrochemical side reactions [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association of Ni nanoparticles has, for all of these reasons, drawing the mind-blowing thought of various specialists for its association. Different techniques for the mix of nickel nanoparticles [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] have been set up, an enormous number of which are followed by an irksome cycle for the separation of nanoparticles, extreme conditions of reaction, and the use of costly reagents, and there is potential to advance new nickel nanoparticles mix methods. To be dynamic in redox works out, phenolic blends, for instance, tannins, flavonoids, and phenolic acids are thought of.…”
Section: Introductionmentioning
confidence: 99%